(untitled) (International Journal of Engineering Management Science, 2022)
This paper proposes a resonant dual-active bridge (DAB) converter, which uses a tuned capacitor inductor–capacitor network. In comparison to the conventional DABs, the proposed topology significantly reduces the bridge currents, lowering both conduction and switching losses and improving the bridge power factors. A mathematical model, which predicts the behavior of the proposed system, is presented to show that both the magnitude and direction of the power flow can be controlled through either relative phase angle or pulse width modulation of voltages produced by the bridges. A mathematical model, which predicts the behavior of the proposed system, is presented to show that both the magnitude and direction of the power flow can be controlled through either relative phase angle or pulse width modulation of voltages produced by the bridges. The viability of the proposed concept is verified through simulation. Experimental results of a 4- kW prototype converter, which has an efficiency of 95% at rated power, are also presented with discussions to demonstrate the improved performance of this topology. In addition, the proposed control plot does not fundamentally build the conduction losses in correlation with the expanded EPS control. In this way, the modified DAB can work efficiently. The topology deduction are first known. At that point, the EPS and TPS regulations are connected, and the comparing working standards and qualities, including the switching, power transfer, and root-mean-square current, are investigated in detail with the help of MATLAB Simulink software with complete results with dynamic response.